Strategi Komunikasi Dan Kolaborasi Jaringan Bisnis Dalam Mengembangkan Usaha Baru Mango Elixirs - Resya Dwi Marselina; Hafiyanti Khanifihaya; Mira Nisaulhaq; Syahrul Rivaldi Irawan; Tito Widianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Developing effective communication strategies and appropriate collaboration in business networks is essential for creating competitive advantages, attracting investors, and expanding business market share. This study will discuss the direct impact of these variables on new business growth and the extent to which their integration can be a determining factor in new business success. Therefore, the researcher chose the research title